Efficiency Analysis of Major Container Ports in Asia: Using DEA and Shannon’s Entropy - Hyun Mi Jang; Ho Park; Sang Youl Kim (International Journal of Supply Chain Management, 2016)
This paper attempts to evaluate performance (i.e. efficiency) of Asias container ports. Measurement of the ports performance is critical to increase the competitiveness of maritime transport, ultimately leading to one nations competitive advantages over other countries. Data Envelopment Analysis (DEA), which is a non-parametric method widely used for assessing efficiency of units which have similar characteristics, was selected to analyse the data. Due to the limitations of the DEA method producing diverse results according to different models, and to the complexities of choosing a specific model among several DEA models, Shannons Entropy was also employed. By including Shannons Entropy, the efficiency results calculated from each model were integrated in order to rank the ports. The results in this study will provide port managers with valuable information in order to understand the current status of Asias container ports in terms of their efficiency.